2020
DOI: 10.1007/s10067-020-05483-9
|View full text |Cite
|
Sign up to set email alerts
|

Which ultrasound lesions contribute to dactylitis in psoriatic arthritis and their reliability in a clinical setting

Abstract: Objectives. To investigate the prevalence of ultrasound elementary lesions in dactylitis in psoriatic arthritis (PsA), and the reliability of scoring these lesions in a clinical setting. Methods. In 31 patients with PsA and clinical dactylitis, ultrasound assessment of the affected digit was performed using grey-scale and color Doppler mode. One examiner scanned all patients and a 2nd examiner scanned 10 patients for inter-reader reliability. The following lesions were evaluated: subcutaneous edema; soft tissu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In particular, in one patient with dactylitis ( Figure 3 ), US findings included soft tissue thickening, subcutaneous edema, flexor tenosynovitis, and synovitis, without major differences with previously-described typical PsA [ 33 ]. US findings of oligoarthritis and monoarthritis patterns showed high levels of SH and PD signals, with no particularities with respect to inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 75%
“…In particular, in one patient with dactylitis ( Figure 3 ), US findings included soft tissue thickening, subcutaneous edema, flexor tenosynovitis, and synovitis, without major differences with previously-described typical PsA [ 33 ]. US findings of oligoarthritis and monoarthritis patterns showed high levels of SH and PD signals, with no particularities with respect to inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, US studies have shown that synovitis and/or flexor TS alongside soft tissue thickening and oedema were the elementary US lesions in dactylitis [ 39 ]. In this work, we did not record the presence of clinical dactylitis in individual joints.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on 12 toes from 7 PsA patients had recorded a similarly high prevalence of tenosynovitis, while joint effusion was only present in a few cases [47]. A recent US study involving 31 PsA patients (17 toes and 12 fingers) showed a high prevalence of soft tissue thickening (81%) and subcutaneous edema (74%) [48]. GS synovitis and GS flexor tenosynovitis were present in 56-68% and 52% of patients, respectively.…”
Section: Imaging Of Foot Dactylitismentioning
confidence: 93%
“…However, it does not include small digital entheses. Signs of enthesitis, though common in dactylitis, present less frequently than other lesions [48]. The reliability of scoring enthesitis of larger entheses has been established in spondyloarthritis [55], but this is not validated for the small digital entheses and needs further exploration.…”
Section: Ultrasound Scoring Of Psa Dactylitismentioning
confidence: 99%